A Picture Series to Help Students Improve Their Narrative Text Writing - Basuki, Anita Dwi; Ariyani, Amra; Iryani, Neni (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The objective of the research was to find out how the picture series can be employed to improve students’ achievement in writing narrative text. This research was a classroom action research. This research consisted of two cycles; each consisted of four stages, namely: planning, acting, observing, and reflecting. The subjects of this research were the Tenth Grade students of SMK Negeri 4 Penajam Paser Utara. In this research the researcher acted as the English teacher. The instruments used to collect the data in this research were an observation sheet, field notes, interview, students’ questionnaire and test. The data analysis of this study was descriptive qualitative and a bit of quantitative measurement to find the percentage of success. Based on the data analysis from each activity, it can be seen that there is a significant difference of the students’ achievement in the pretest and posttest. The students’ achievement in the posttest is higher than that of the pretest. The finding of the research indicated that the picture series could improve the students’ achievement in writing narrative text. The improvement can be seen from the increase of the students’ assessment from preliminary test, cycle one and cycle two. In preliminary study that just 10 students (37%) passed the preliminary test, while 27 students (63%) students were unsuccessful. There was just one student who got excellent grade. In the first cycle only thirteen students or 48% got less than 60, four students or 15% got only passing grade that is 60, eight students or 30% got 70, one students or 7% got 75. And in the second cycle there was significant improvement. There were just 3 students (11%) got less than 60. Another 24 students (89%) got higher than passing grade. It was suggested that the English teachers employ the picture series to improve students’ achievement in writing narrative text. However, to get the passing score of the test in this research should be planned carefully. Finally, other researchers, one suggested employing picture series would bring the students to the freedom of expressing their feeling in writing. It built their self confident automatically.